2019
DOI: 10.2298/vsp171201007j
|View full text |Cite
|
Sign up to set email alerts
|

Fecal galectin-1 as a potential marker for colorectal cancer and disease severity

Abstract: Background/Aim. Colorectal cancer (CRC) represents one of the most common cancers worldwide. CRC is frequently diagnosed at advanced stages with poor prognosis, indicating the need for new diagnostic and prognostic markers. The aim of this study was to determine systemic and fecal values of galectin-1 (gal-1) and ratios between gal-1 and proinflammatory cytokines: tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β) and interferon gamma (IFN-γ), in the patients with CRC and the relationship with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Anti-inflammatory role of Gal-1 is reflected in the fact that it converted macrophages from their proinflammatory to anti-inflammatory profile thus terminating the inflammation 29 . Our previous work revealed predomination of Gal-1 over proinflammatory cytokines in patients with colorectal cancer, suggested on the immunomodulatory function of Gal-1 in the restriction of inflammation 30 . Our results confirmed the results of previous studies that systemic levels of proinflammatory cytokines IL-1 and IL-6 are rising during the progression of COVID-19 suggesting on ongoing development of inflammation 31 .…”
Section: Discussionmentioning
confidence: 90%
“…Anti-inflammatory role of Gal-1 is reflected in the fact that it converted macrophages from their proinflammatory to anti-inflammatory profile thus terminating the inflammation 29 . Our previous work revealed predomination of Gal-1 over proinflammatory cytokines in patients with colorectal cancer, suggested on the immunomodulatory function of Gal-1 in the restriction of inflammation 30 . Our results confirmed the results of previous studies that systemic levels of proinflammatory cytokines IL-1 and IL-6 are rising during the progression of COVID-19 suggesting on ongoing development of inflammation 31 .…”
Section: Discussionmentioning
confidence: 90%
“…Our previous study has also shown importance of Galectin-1 in the pathology of CRC. We noticed fecal Gal-1 in feces samples of patients with more advanced form of CRC [11] . Moreover, Gal-1 positively correlates tumor markers, such as AFP and CA 19-9 and with tumor histological differentiation stage [11] .…”
Section: Discussionmentioning
confidence: 74%
“…We noticed fecal Gal-1 in feces samples of patients with more advanced form of CRC (11). Moreover, Gal-1 positively correlates tumor markers, such as AFP and CA 19-9 and with tumor histological differentiation stage (11). According to available information, this is the first research, which investigates connection between systemic Gal-1 and anemia in CRC patients.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Galectin-1 consistently manifests heightened expression within tumor tissues, encompassing not only the neoplastic cells but also the accompanying stromal cells [16]. Notably, it plays a significant role in the carcinogenesis of colorectal tumors [57][58][59]. Such heightened levels are often indicative of a more aggressive tumor behavior, promoting the development of a metastatic phenotype [60].…”
Section: Galectin-1 In Oncology: From Tumor Progression To Therapeuti...mentioning
confidence: 99%